EFFECTIVENESS OF COMMUNITY SERVICE MODEL FOR INCREASING ROUTINE IMMUNIZATION COVERAGE AT PRIMARY HEALTHCARE FACILITIES IN A RURAL DISTRICT OF PAKISTAN: A QUASI-EXPERIMENTAL STUDY - Ali, Zulfiqar; Pongpanich, Sathirakorn; Kumar, Ramesh (Journal of Ayub Medical College Abbottabad, 2015)
Background: In Pakistan Routine Immunization coverage has been reported to be significantly low due to multiple factors that results in high number of deaths in children under 5. This study was conducted to assess the effectiveness of integrating Community Services to improve Routine immunization coverage in rural district of Pakistan. Methods: A quasi-experimental study with control and intervention arms was conducted in government Basic Health unit's catchment population of Panjgur by interviewing household head/Fathers. Total 234 household head including fathers were interviewed during this baseline survey. Community service model was used for to increase routine immunization coverage at catchment area of Basic Health unit (BHU) in intervention group while routine services were given in control BHU. Results: 230 parents completed the questionnaire during the end line after three months of intervention. There were no significant differences found between two groups at baseline but after the intervention, there was statistically significance difference (<0.05) between both group's knowledge and practices regarding routine immunization. Moreover, there was no statistically significant difference in control group reported (>0.05) after the intervention period. Overall immunization status after intervention where fully immunization status in intervention group after intervention was 88.8% as compared to control group after intervention was 13.6% for partial immunization status in intervention group after intervention was 11.1% as compared to control group after intervention was 81.1 for the Non-Immunization status in intervention group after intervention was 0% as compared to control group after intervention was 5.1%. Conclusions: Community Service Model has significantly improved the Knowledge & Practices among households/parents of children under 5 in the intervention arm.